The Benefits of Tariff Reductions in the Presence of Psychological Adjustments Costs - Tompkinson, Paul (School of Management Working Papers, 1996)
A model of a small trading economy is developed which introduces the notion of "psychological adjustment costs". This model is then employed to consider the welfare effects of tariff reduction. It is assumed that the government is only prepared to eliminate the existing tariff if this action generates a potential Pareto improvement. It is then shown that the policy which satisfies this restriction and which 1s implementable provides only consumption gains from trade.